Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm currently trying to prove that $\sum_{k=1}^\infty t_k$ diverges, where $$t_k = \frac{(-1)^k+1}{2k}+ \frac{(-1)^k}{\sqrt{k}}$$

I know that $\sum_{k=1}^\infty \frac{(-1)^k}{\sqrt{k}}$ converges by the alternating series test, and that the series $\sum_{k=1}^\infty \frac{(-1)^k+1}{2k}$ diverges, as it's just a scaled harmonic series interspersed with zeros.

My question is: is it correct to say that the series in question diverges because it is the sum of a convergent series and a divergent series? It seems pretty straightforward if this is allowed, but I'm worried that I'm missing some subtlety about saying $\sum t_k = \sum_{k=1}^\infty \frac{(-1)^k}{\sqrt{k}} +\sum_{k=1}^\infty \frac{(-1)^k+1}{2k}$, (i.e., rearranging the terms in the sum), since the convergent part is only conditionally so.

Would someone please be able to clarify if such a subtlety exists, or if what I've done is alright? Thanks!

share|cite|improve this question
You are right to ne cautious. But look at the sum $S_n$ of the first $n$ terms, $n$ large. The part due to $1/2+1/4+\cdots$ is (kind of) big, while the part due to the $\sum_1^n (-1)^n$ doesn't get very negative, indeed stays abovve $-1$. So $S_n$ is kind of big. – André Nicolas Feb 7 '13 at 22:51
up vote 2 down vote accepted

If $\displaystyle{\sum_{k=1}^\infty a_k=a, \ \sum_{k=1}^\infty b_k=b}$ then $\displaystyle{\sum_{k=1}^\infty (a_k+b_k)=a+b}$.

Now if your series, $\displaystyle{\sum_{k=1}^\infty t_k}$, converges then the series $\displaystyle{\sum_{k=1}^\infty t_k+s_k}$, where $s_k=\dfrac{(-1)^{k+1}}{\sqrt{k}}$, converges ↯.

share|cite|improve this answer
That helped, thanks! – sourisse Feb 7 '13 at 21:54


Write your general term as $$ t_k=a_k+b_k+c_k $$ in such a way that $\sum a_k$ and $\sum b_k$ converge by Leibniz criterion for alternating series, and $\sum c_k$ diverges because it is a constant times the harmonic series.

If $\sum t_k$ converged, then so would $\sum t_k-a_k-b_k=\sum c_k$. A contradiction.

So your series diverges.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.